Samsung galaxy tab 4 nook for dummies - Sandler, Corey (Indianapolis, IN : John Wiley and Sons, 2014)
Nearly everything you can do on a desktop or laptop computer can now be accomplished on a small. battery-operated handeld recrangle of plastic an glass. The best way to think of a tablet like the Samsung Galaxy tab 4 NOOK is as a super - sized smartphone, without the cellular phone connection
Tặng
Keywords: Portable computers; Samsung Galaxy Tab (Computer); Tablet computers; Portable computers; Samsung Galaxy Tab (Computer); Samsung Galaxy Tab (Computer) -- Handbooks, manuals, etc; Tablet computers -- Handbooks, manuals, etc; Tablet computers